INNOVATIVE DEVELOPMENT OF UKRAINE - Voloshchuk, Kateryna; Voloshchuk, Vitaliy; Voloshchuk, Yuliia (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
It is determined that in economic science there is no single approach to the interpretation of the concept of ‘innovation’. It is suggested that taking into account the radical changes that are in the world economy today it is necessary to use the extended concept of innovation, which should be understood as the results of the development transformation, research, ideas and their combination into a radically new or improved technological, economic, social solution, the results of which can be applied in practice. The main indicators that determine the level of innovation development of a country or region and provide an opportunity to determine the impact on economic development are covered. The place of Ukraine in such ratings according to indicators of innovative development in 2017, 2018 and problems that cause their low level are defined. The improvement directions of the innovative development level of the country are defined and the real steps taken by the government of the country to correct the negative trends through the introduction of digital transformation of the country’s economy, the transition from raw material to high-tech production and the basis of innovative IT technologies and communications are shown.